2005
DOI: 10.1021/om050891p
|View full text |Cite
|
Sign up to set email alerts
|

Iron Complexes Bearing 2-Imino-1,10-phenanthrolinyl Ligands as Highly Active Catalysts for Ethylene Oligomerization

Abstract: A series of iron complexes ligated by 2-imino-1,10-phenanthrolinyl ligands, LFeCl 2 (L ) 2-(ArNd CR)-1,10-phen), were synthesized and sufficiently characterized by elemental and spectroscopic analysis along with X-ray diffraction analysis. Activated with methylaluminoxane (MAO) or modified methylaluminoxane (MMAO), these iron(II) complexes show high catalytic activities up to 8.95 × 10 7 g mol -1 (Fe) h -1 for ethylene oligomerization. The distribution of oligomers produced follows Schluz-Flory rules with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 37 publications
6
104
0
Order By: Relevance
“…93 In addition, 35 it was found that the substituent on the arylimino moiety affected the product formed, for example, for the phenyl bearing an Et substituent, ie 172b, the best activity was observed, whilst stronger electron withdrawing groups decreased the ethylene reactivity (when the phenyl substituent 40 R 1 was a halogen, the activity order decreased as follows: Br > Cl > F). 91 Variation of the R substituent on the imino-C of ligands of the type, 2-(ArN=CR)-1,10-phenanthroline, also resulted in changes to the catalytic performance. The aldimine (R = H, 172a), ethyl-ketimine (R = Et, 172c) and phenyl-45 ketimine (R = Ph, 172d) complexes showed relatively lower catalytic activities than did the corresponding methyl-ketimine (R = Me, 172b) complex.…”
Section: Other Tri-dentate Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…93 In addition, 35 it was found that the substituent on the arylimino moiety affected the product formed, for example, for the phenyl bearing an Et substituent, ie 172b, the best activity was observed, whilst stronger electron withdrawing groups decreased the ethylene reactivity (when the phenyl substituent 40 R 1 was a halogen, the activity order decreased as follows: Br > Cl > F). 91 Variation of the R substituent on the imino-C of ligands of the type, 2-(ArN=CR)-1,10-phenanthroline, also resulted in changes to the catalytic performance. The aldimine (R = H, 172a), ethyl-ketimine (R = Et, 172c) and phenyl-45 ketimine (R = Ph, 172d) complexes showed relatively lower catalytic activities than did the corresponding methyl-ketimine (R = Me, 172b) complex.…”
Section: Other Tri-dentate Ligandsmentioning
confidence: 99%
“…However, upon treatment with MAO or MMAO, 172c, which bears an ethyl substituent 50 on the imine-C, revealed a better thermal stability (10 °C higher compared to 172b) and possessed a higher content of α-olefins (C6-C16). 91,94,95 When a phenyl substituent was introduced at the 9-position of the 1,10-phenanthroline by reaction of PhLi with 2-acetyl-1,10-phenanthroline, the 55 resultant 2-imino-9-phenyl-1,10-phenanthrolines complexes 174a, 174b, 174d exhibited much lower activities (2.33 × 10 6 g mol -1 h -1 ) in comparison to their analogues 172a-d, and the products included butene (major product, > 90 %) and hexene; there was no polymer formation. 96 Replacement of the imine 60 group with benzimidazoles resulted in iron complexes of type 176, bearing 2-(benzimidazol-2-yl)-1,10-phenanthrolines.…”
Section: Other Tri-dentate Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the 2,6-bis(imino)pyridine ligand frame has continued to lead the way, the past 10 years has also seen the development of alternative ligand sets that can act as compatible supports for iron and cobalt ethylene oligomerisation/polymerisation catalysts ( Table 4 ) [46,50,181,182,183,184,185,186,187,188,189,190,191,192,193,194,195,196,197,198,199,200,201,202,203,204,205,206,207,208,209] ; active catalysts based on bimetallic iron and cobalt precatalysts have also started to emerge ( Table 5 ) [54,210,211,212,213,214,215] . In the main, these systems show lower activities than the prototype bis(imino)pyridine-based catalysts, although several of these systems have significantly started to approach their catalytic performances (e.g.…”
Section: Alternative Iron and Cobalt Catalystsmentioning
confidence: 99%
“…In addition to the P ∧ O chelating nickel complexes used in the SHOP process, [2,6] there are numerous nickel catalysts being investigated with bidentate ligands, such as N ∧ O, [7,8] P ∧ N, [9,10] and N ∧ N, [3,[11][12][13] and tridentate ligands, such as N ∧ N ∧ O, [14] N ∧ P ∧ N, [15] P ∧ N ∧ P, [16] P ∧ N ∧ N, [13d,16] and N ∧ N ∧ N, [17,18] as well as organometallic compounds. [15a] Considering N ∧ N ∧ N tridentate nickel complexes as catalysts for ethylene oligomerization, several models with high activities have been developed in our group by using 2-imino-1,10-phenanthrolines (A), [18b] 2-(2-benzimidazole)-6-iminopyridine (B) ligands, [19] and 6-imino-2-quinoxalinylpyridines.…”
Section: Introductionmentioning
confidence: 99%